FAST FORWARD? Reflections on fashion and modernity - Verschueren, Alexandra (Public Journal of Semiotics, 2011)
This article starts from the striking obsession of the fashion world with innovation and change. Then a systematic attempt is made to relate this feature to the notions of modernity, modernism, and post-modernity. An exploration of these notions in relation to each other leads to a description of the position of fashion in the economy, in a world imbued with social status and politics, in the sphere of individuality and individual needs, and in the context of art and culture. A complex picture emerges in which the artistic and practical problems faced by a designer can be summarized in the following question: what can be made how and where in a sufficiently creative and innovative way, appealing to people’s ambivalent needs for identity, conformity, and individual self-expression, and producible in an affordable and ethical manner?